Design of high-efficiency CMOS rectifier with low reverse leakage for RF energy harvesting - Kim, Hyeonwoo; Kwon, Ickjin (Electronics Letters, 2019)
A CMOS cross-coupled RF rectifier that improves power conversion efficiency (PCE) with low reverse leakage current for energy harvesting wireless sensors is proposed. In this Letter, the authors propose a CMOS cross-coupled differential RF rectifier that uses a thick-oxide MOSFET as a rectifying device to improve PCE by reducing reverse leakage current. The proposed rectifier is designed for UHF band application using 0.18 µm CMOS technology. Proposed rectifier achieves a peak PCE of 75.2% and sensitivity of − 17 dBm for 1 V output voltage. Peak PCE is improved by 8.8% compared to the conventional rectifier.
Keywords: CMOS technology; High-efficiency; Output voltages; Power conversion efficiencies; Rectifying devices; Reverse leakage current; RF energy harvesting; Wireless sensor